The effects of pithecellobium jiringa, morinda elliptica and pluchea indica water extracts on glucose absorption in in vitro models - Syamsul bin Ahmad Arifin (Kulliyyah of Pharmacy, International Islamic University Malaysia, 2010)
Post-prandial hyperglycemia is an independent risk factor for the development of complications in diabetes patients. Uncontrolled dietary intake of polysaccharide has been shown to aggravate the postprandial hyperglycemia. The study was geared to fulfill the strategy by screening several plants that have potential to be used as antidiabetic agents namely Pithecellobium jiringa (seeds and pericarp), Morinda ellipticA and Pluchea indica in inhibiting the glucose absorption in vitro model. The everted sac preparation and intestinal perfusion system were employed to screen the glucose absorption inhibitory actions of the plant extracts followed by in vivo studies in normal and streptozotocin induced diabetic rats. The crude water extract of P. jiringa (pericarp) showed appreciable effect in lowering the glucose absorption and also inhibition of digestive enzyme in the everted sac and intestinal perfusion system. On the other hand, the seeds of P. jiringa also exhibited inhibition of glucose absorption in the everted sac preparation and inhibition of digestive enzyme when tested in perfusion system. Hypoglycaemic test in normal rats revealed that only extract from M. elliptica and P. indica showed significant different (p<0.05). None of the extracts tested significantly (p>0.05) reduced blood glucose levels in diabetic rats. The antihyperglycemic test on normal rats also onstrated insignificant (p>0.05) finding in lowering blood glucose levels. However, when tested in diabetic rats, only pericarp of P. jiringa and P. indica significantly (p<0.05) reduced the blood glucose levels. The repeated doses administration of the crude water extracts of seeds and pericarp of P. jiringa for 10 days significantly reduced the fasting blood glucose in diabetic rats compared to pre-treatment level. The study was also able to demonstrate the usefulness of the in vitro model of the improvised intestinal perfusion system in screening plant extract effects on glucose absorption in the intestine. The results suggested that the inhibition of digestive enzymes and inhibition of glucose absorption are the most probable mechanism of action of the P. jiringa extracts in exhibiting its antihyperglycaemic activity. The study proposing that the pericarp and seed P. jiringa extract to be further studied and developed as agent to avoid post prandial hyperglycaemia and prevent complication.